2010
DOI: 10.1016/j.jpsychires.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of human insular cortex and insular volume reduction in Williams syndrome

Abstract: Functional imaging in humans and anatomical data in monkeys have implicated the insula as a multimodal sensory integrative brain region. The topography of insular connections is organized by its cytoarchitectonic regions. Previous attempts to measure the insula have utilized either indirect or automated methods. This study was designed to develop a reliable method for obtaining volumetric magnetic resonance imaging (MRI) measurements of the human insular cortex, and to validate that method by examining the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…By using six axially acquired, intensitynormalized, registered, and averaged T1-weighted 1.5 T structural MRIs (0.9375 × 0.9375 × 1.2 mm; GE) (23) for each participant, we assessed structural integrity of insular gray matter in two ways: a volume-of-interest (VOI) and a voxel-wise approach. First, for the VOI analysis, an operator blinded to diagnostic information manually delineated each individual's insulae in native space, in line with Cohen et al (39), using ITKSnap software (http://www. itksnap.org/).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using six axially acquired, intensitynormalized, registered, and averaged T1-weighted 1.5 T structural MRIs (0.9375 × 0.9375 × 1.2 mm; GE) (23) for each participant, we assessed structural integrity of insular gray matter in two ways: a volume-of-interest (VOI) and a voxel-wise approach. First, for the VOI analysis, an operator blinded to diagnostic information manually delineated each individual's insulae in native space, in line with Cohen et al (39), using ITKSnap software (http://www. itksnap.org/).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the AI is cytoarchitectonically characterized by marked abundance of von Economo neurons (35), which are also selectively present elsewhere in the so-called "salience network" (36), including the OFC and ACC, of humans and nonhuman primates (37); these neurons may play an important role in regulating executive control relevant for emotional awareness (4,35,37,38). These findings, together with reports of structural perturbations of the AI (39), suggest that the human insula, especially the AI, is a neural target through which the genetically determined atypical empathy, nonsocial anxiety, and hypersocial WS personality (12)(13)(14)(15)29) may be mediated. The insula's integral role in both the brain circuits and behaviors that are prominently affected in WS formed the basis of our hypothesis-driven investigation of this region in WS.…”
mentioning
confidence: 96%
“…We were additionally interested in the amygdala, a subcortical structure that has extensive structural (Augustine, 1996;Nieuwenhuys, 2012) and functional connections with the insula (Stein et al, 2007;Roy et al, 2009;Robinson et al, 2010;Cauda et al, 2011). An inverse relationship between changes in insula and amygdala volumes has been reported in certain pathological conditions such as Williams syndrome (Cohen et al, 2010), while enlargement of the amygdala has also been demonstrated in major depressive disorder (Frodl et al, 2003;Hamilton et al, 2008) and chronic social stress (Davidson and McEwen, 2012). We compared ADPs with healthy volunteers and hypothesized that alcohol dependence is associated with: (i) a decreased volume of the anterior insula, normalized to total brain volume; (ii) an increased volume of the amygdala, normalized to total brain volume; and (iii) an increased ratio of the volumes of the amygdala and insula.…”
Section: Introductionmentioning
confidence: 97%
“…Reductions in insular surface or grey matter volume have been reported in patients with several psychiatric disorders, including schizophrenia (Takahashi et al, 2005), fragile X syndrome (Cohen et al, 2011), and Williams syndrome (Cohen et al, 2010), while an increase in anterior insula volume was reported in obsessive-compulsive disorder (Nishida et al, 2011). Little is known, however, about potential structural pathology of the insular cortex in alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from studies of individuals with WS have indicated that, relative to total brain graymatter volume, the gray matter volume of the amygdalae was significantly larger bilaterally for individuals with WS who had ID than for CA-matched TD controls [97][98][99], but did not differ significantly from TD CAmatched controls for individuals with WS who had low average or average IQ [100]. Structural findings for the insula have been inconsistent, with some studies of individuals with WS who had ID indicating bilateral increase [98,101] and others indicating bilateral reduction [102] relative to total brain gray-matter volume. More complex findings were reported for individuals with WS who had low average to average IQs, with bilateral reduction in dorsal anterior insula but increase in the right ventral anterior insula [103].…”
Section: Neural Underpinnings Of Social Referencingmentioning
confidence: 99%